Toy story [videorecording (DVD)] - Lasseter, John; Lasseter, John; Hanks, Tom; Allen, Tim, 1953-; Varney, Jim; Ratzenberger, John (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
An astonishing world where toys play while their owners are away. Woody is a pull-string cowboy doll and is the leader of the toys until the latest, greatest action figure, Buzz Lightyear, enters the picture. When the toy rivals are separated from their owner, they learn to put aside their differences and work as a team to get back home to the boy they love.